Types and forms of resilience in local planning in the U.S.: Who does what?. Issue 88 (October 2018) - Keenan, Jesse M.
Abstract: This paper presents and analyzes the results of a survey of actors (n = 130) engaged in planning activities in local governments in the United States (U.S.). This exploratory survey was designed to evaluate the nature of existing resilience, climate change and multi-hazard planning activities, if any, as well as additional considerations for understanding the general state of awareness and knowledge of resilience activities and strategies among various public sector actors. The survey data tests several hypotheses, including the hypothesized disproportionate activity of large cities; the positive correlation between resilience, hazard mitigation and emergency planning; and, the dominate usage of disaster and engineering conceptual variants of resilience. Data from the survey provides evidence in support of an affirmation of the hypotheses. The paper offers insight into the dominate actors and frames that are driving resilience planning, as well as the challenges faced by a lack of discipline for applying categorical variants of resilience.